Teori Hukum Progresif dalam Konsep Negara Hukum Indonesia - Siregar, Mardona (Muhammadiyah Law Review Journal, 2024)
Progressive Legal Theory is a legal theory that changes rapidly makes fundamental reversals in legal theory and practice, and makes various breakthroughs. This liberation is based on the principle that law is for humans and not vice versa and that law does not exist for itself but for something broader, namely for human dignity, happiness, welfare, and human glory. Through an analysis of various cases and legal policies in Indonesia, this article attempts to show how progressive legal theory can be the basis for more inclusive and equitable legal reform. This type of research is qualitative, using data from the literature; the data is then analyzed using descriptive techniques. The results of this study indicate that progressive legal theory offers a dynamic and responsive approach to responding to social developments and community needs. In the context of the Indonesian rule of law, this theory emphasizes the importance of flexibility and adaptability of law to realize substantive justice